Pyrrolidine Catalyzed Direct Synthesis of 3,5-Diarylcyclohexenones from Acetone and Chalcones - J. Wagh, Sandip; Chowdhury, Raghunath; K. Ghosh, Sunil (Current Organocatalysis, 2014)
The organo-catalyzed reaction of chalcones with acetone has been described. Pyrrolidine has been found to catalyse the cascade Michael-aldol-dehydration of chalcones and acetone to produce 3,5-diaryl cyclohexenones under mild conditions with good yields. The organocatalytic methodology tolerated a range of substituents on both the aromatic rings of chalcones. The cyclohexenones produced are known to be the precursors for 3,5-diarylphenols, 3,5-diarylanilines and complex heterocycles.
Keywords: organocatalysis